DYNAMICS OF MICRODESTRUCTION IN ELASTIC ZONE DURING EXPLOSION OF SPHERICAL CHARGE - Sher E.N.; Aleksandrova N.I. (My University, 2001)
Kinetic parameters of in elastic zone of rock mass deformed with explosion have been considered. Action of explosion on the rocks has been discussed. Mathematical model of explosion of concentrated charge in rock has been developed. Accumulation of damages in elastic zone under action of blast wave has been taken into account in the model. Condition at which density of microcracks achieves critical value is used as criterion of destruction. Rate of growth of the microcracks is determined by exponential function of equivalent stress. Density of microdefects is found under condition that arising of microcracks occurs at constant rate at given tensile stress.